Pengembangan Media Busy Book Berbasis pendekatan Kontekstual dalam Meningkatkan Keterampilan Motorik Halus Anak Usia Dini 4-6 Tahun di Tk Negeri Pembina Singaraja - Warnalina Nazara; I Made Tegeh (Universitas Pendidikan Ganesha, 2023)
Childhood is a very suitable period to stimulate the development of fine motor skills. This research aims to develop Busy Book media based on a contextual approach to improving early childhood fine motor skills. This research includes development research using the ADDIE Model. The subjects in this study used 2 media experts, 2 material experts, 1 practitioner expert, 3 children in individual trials, and 10 small group trials. Data collection in this research used a questionnaire method, which was then analyzed using data analysis, namely quantitative and qualitative data. The results of the research stated that the Busy Book media was declared valid with very good qualifications from experts with a percentage of material expert validity results obtained with a score of 98.5%, media expert validity results obtained with a score of 90.5%, practitioner validity results obtained with a score of 91%, test validity results individuals obtained a score of 95%, and the results of the validity of the small group test obtained a score of 98%. From these results, the development of Busy Book media based on a contextual approach to improving the fine motor skills of early childhood children 4-6 years old is suitable for use.